The Impact of NPK 16-20-16 Fertilizer Application on Increasing Eggplant (Solanum melongena L.): Dampak Aplikasi Dosis Pupuk NPK 16-20-16 Terhadap Peningkatan Hasil Panen Tanaman Terong (Solanum melongena L.) - Puspita, Fadia Nasalita; Abror, M. (Procedia of Engineering and Life Science, 2025)
This study aims to determine the impact of applying different doses of NPK fertilizer (16-20-16) on the yield performance of eggplant (Solanum melongena L.). The research was conducted at the experimental field using a Randomized Complete Block Design with four fertilizer treatments: 0 g/plant, 5 g/plant, 10 g/plant, and 15 g/plant. Parameters observed included plant height, number of leaves, number of flowers, fruit set, fruit weight, and total yield per plant. The results indicated that NPK fertilizer application significantly improved eggplant growth and yield. The 10 g/plant dose produced the best performance in terms of fruit weight and total yield, while excessive dosage (15 g/plant) did not further increase yield significantly. Therefore, optimal NPK application can enhance eggplant productivity in sustainable farming systems.